Into the magic shop : a neurosurgeon's quest to discover the mysteries of the brain and the secrets of the heart - Doty, James R. (James Robert), 1955- (Avery, an imprint of Penguin Random House, 2016)
The author relates how a chance encounter in a magic shop with a woman who taught him exercises to ease his sufferings and manifest his greatest desires gave him a glimpse of the relationship between the brain and the heart, and drove him to explore the neuroscience of compassion and altruism.